2017
DOI: 10.1093/glycob/cwx109
|View full text |Cite
|
Sign up to set email alerts
|

A competitive alphascreen assay for detection of hyaluronan

Abstract: A method for specific quantification of hyaluronan (HA) concentration using AlphaScreen® (Amplified Luminescent Proximity Homogeneous Assay) technology is described. Two types of hydrogel-coated and chromophore-loaded latex nanobeads are employed. The proximity of the beads in solution is detected by excitation of the donor bead leading to the production of singlet oxygen, and chemiluminescence from the acceptor bead upon exposure to singlet oxygen. In the HA assay, the donor bead is modified with streptavidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Meanwhile, the high signal-to-background ratio, high dynamic range, high sensitivity and wash-free procedure associated with the ALPHA makes this technology suitable for HTS application, allowing for the discovery of hits from a big library of compounds [39][40][41]. In addition to the application of screening enzyme or protein inhibitors [42,43], the ALPHA has also been utilized to quantify the concentrations of proteins [44,45], DNAs [46] or small molecules [47], and to capture PPI [48,49], as well as to characterize ternary complexes formed between a target protein, a PROTAC degrader and an E3 ligase [25,29,34,50,51]. Detecting ternary complex formation is one of the most ueful applications of the ALPHA for PROTAC degraders.…”
Section: Amplified Luminescent Proximity Homogeneous Assaymentioning
confidence: 99%
“…Meanwhile, the high signal-to-background ratio, high dynamic range, high sensitivity and wash-free procedure associated with the ALPHA makes this technology suitable for HTS application, allowing for the discovery of hits from a big library of compounds [39][40][41]. In addition to the application of screening enzyme or protein inhibitors [42,43], the ALPHA has also been utilized to quantify the concentrations of proteins [44,45], DNAs [46] or small molecules [47], and to capture PPI [48,49], as well as to characterize ternary complexes formed between a target protein, a PROTAC degrader and an E3 ligase [25,29,34,50,51]. Detecting ternary complex formation is one of the most ueful applications of the ALPHA for PROTAC degraders.…”
Section: Amplified Luminescent Proximity Homogeneous Assaymentioning
confidence: 99%
“…( Figure 3 ). Strong binding of HABP and HAPLN1 to HA still occur under the conditions used, and have been previously studied and exploited in development of a sensitive and specific competitive AlphaScreen assay for HA ( Huang et al, 2018 ). Protein binding to HA, in the absence of protein self-association in a manner that can link two end-biotinylated HA chains together (for example, side-by-side association on a single HA polymer) is not sufficient for the observation of HA crosslinking using streptavidin-coated donor and acceptor beads in the AlphaLISA assay.…”
Section: Resultsmentioning
confidence: 99%
“…The 50 kDa bHA chains are about 125 nm long. In our previous AlphaScreen studies of direct binding between HA and proteins on donor and acceptor beads respectively, the length of 50 kDa HA was found to provide an optimum spacing for signal, whereas HA of higher molecular weight (250–1000 kDa) gave reduced signal due to increased bead-to-bead distance ( Huang et al, 2018 ). AlphaScreen and AlphaLISA methods differ in the identity of the chromophores inside the acceptor beads, and the choice of platform for the present studies was driven by commercial availability of acceptor beads with streptavidin coating.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies revealed a great potential of HA as a biomarker of pathophysiology and inflammation for diagnostic applications [ 4 ]. Currently, the most common method for quantitative detection of HA is enzyme-linked immunosorbent assay (ELISA)-like technique, where HA-binding proteins (HABPs) are utilized as detection agents in competitive and sandwich assays [ 5 , 6 ]. While HA concentration in the biological fluids can be successfully determined, this method is labor-intensive and time-consuming due to the need of multiple washing steps.…”
Section: Introductionmentioning
confidence: 99%